Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Prestasi Belajar IPAS pada Materi Nilai-Nilai Tradisi di Indonesia di Kelas 3 Sekolah Dasar - Vidu, Sramanera Badra; Badarudin, Badarudin (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The low academic achievement of third-grade students at SDN 2 Banteran was the background for this study. The purpose of this study was to determine the improvement in student academic achievement in learning traditional values in Indonesia through the jigsaw cooperative model in third-grade elementary school. This study used classroom action research with four stages, including planning, implementation, observation, and reflection. Data collection techniques in this study include observation sheets, evaluation questions, and documentation. The research subjects are third-grade students at SDN 2 Banteran. The research data were analyzed descriptively by examining student scores. The results showed an improvement in learning achievement in Cycle I, with 70% of students meeting the minimum completion criteria, increasing to 80% in Cycle II. The findings of this study on the application of the jigsaw cooperative model indicate that the application of the jigsaw cooperative model can improve student learning achievement.Prestasi belajar siswa di kelas III SDN 2 Banteran masih rendah, melatarbelakangi penelitian ini. Penelitian ini memiliki tujuan guna mengetahui peningkatan prestasi belajar siswa dalam pembelajaran nilai-nilai tradisi di Indonesia melalui model kooperatif tipe jigsaw di kelas III Sekolah Dasar. Penelitian ini memakai Penelitian Tindakan Kelas dengan empat tahapan meliputi perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data dalam penelitian ini memakai lembar observasi, soal evaluasi, dan dokumentasi. Subjek penelitian ini adalh siswa kelas III SDN 2 Banteran. Data hasil penelitian dianalisis secara deskriptif dengan melihat nilai siswa. Hasil menunjukan terdapat peningkatan prestasi belajar pada siklus I prestasi belajar siswa sebesar 70% siswa mencapai kritetia ketuntasan minimal meningkat menjadi 80% pada siklus II .Temuan penelitian pada penerapan model kooperatif tipe jigsaw menunjukan penerapan model kooperatif tipe jigsaw bisa meningkatkan prestasi belajar siswa.